Kompetensi Profesional Guru Melalui Supervisi Akademik Kepala Sekolah Pada SMA Negeri 3 Karimun Kepulauan Riau Semester I Tahun 2018/2019 - Khairani Khairani (STKIP ROKANIA, 2023)
The school principal has the task of advancing and carrying out academic supervision of teachers, so that with academic supervision it is hoped that it can increase teacher professionalism. The purpose of this study was to find out and analyze the influence of the principal's academic supervision on the professional competence of teachers at SMA Negeri 3 Karimun Kepulauan Riau. This research method uses a qualitative approach with a type of case study research (intrinsic case study). The results of the study seen from the comparison test of the magnitude of the difference conducted on the academic supervision of the principal of SMAN 3 Karimun Kepulauan Riau, there is no significant difference between the academic supervision of the principal at SMAN 3 Karimun Kepulauan Riau, because based on the calculation results, the calculated t value using the polled variance is – 0.103 and consulted with the price of the t table with an error rate of 5%, the price of the t table is 1.98. So t count, is in the area of ​​acceptance of Ho (located between table prices), then Ho is accepted and Ha is rejected. This also occurs in the magnitude of differences in teacher professional competence, the results of which are no significant differences between the professional competence of teachers at SMAN 3 Karimun Kepulauan Riau because based on the calculation results, the calculated t value using polled variance is -0.041 and consulted with the t table price with the level error is 5% then the price of t table is 1.671. So t count, is in the area of ​​acceptance of Ho (located between table prices), then Ho is accepted and Ha is rejected. So that the two comparative hypotheses proposed were rejected because there was no significant difference in the academic supervision of the principal and the professional competence of teachers at SMAN 3 Karimun Kepulauan Riau